Flexural properties of cellulose nanofibre reinforced green composites - Dong, Jonathan; Takagi, H. (Elsevier, 2014)
A study on the flexural properties of environmentally friendly "green" composites made from starch-based, dispersion-type biodegradable resin and cellulose nanofibres is presented in this paper. Models were developed for correlating the flexural modulus and flexural strength with voids and fibre length-diameter ratio due to processing. It shown voids and fibre length-diameter ratio have large effect on the flexural modulus. The flexural modulus decreases with increasing void content and increases with fibre length-diameter ratio. Thus, the flexural modulus can be increased by choosing the processing method. This study shows the stirrer mixing process yields the highest average fibre length-diameter ratio. Flexural strength decreases as expected with increasing void content. The stirrer mixing process yields the highest overall flexural strength, which is due to the lowest void content and enhanced uniform dispersion of nanofibres. It can be derived from the regression model that flexural strength is dependent on the average fibre length-diameter ratio, and the critical fibre length-diameter ratio for reinforcing the matrix is about 80. The sensitivities of the flexural strength to voids were also studied, and it was found that the stirrer-treated composites were least sensitive to voids.